Imam Muslim and the Methodology of Compiling the Book of Ṣaḥiḥ Muslim - Asyraf, M. Asyraf Mubarak Sudarmin (Ihyaussunnah : Journal of Ulumul Hadith and Living Sunnah, 2023)
This paper discusses Imam Muslim, who is known for his book of Muslim, and his method of preparing the book of ṣaḥiḥ. Although Imam Muslim had special requirements for the book's preparation, they were not as strict as Imam Bukhari's. The research for this paper used primary sources from various literature related to Imam Muslim and the book of ṣaḥiḥ Muslim, and employed a qualitative approach to explore the matters related to Imam Muslim. The data sources included primary and secondary data from books, journals, and literature. The paper describes the special requirements for the preparation of the book of Muslim in a clear and concise manner for the reader's convenience.